Perbandingan Efektivitas Penambahan Tramadol 0,125 Mg/Kgbb/Jam dengan Tramadol Bolus Intermitten 50mg Per 6 Jam pada Pasien yang Mendapatkan Fentanil 1 Μg/Kgbb/ Jam untuk Penanganan Nyeri Pasca Operasi - Noegroho, Wahyu; Uyun, Yusmein; Widodo, Untung (This journal is published by the Department of Anesthesiology and Intensive Therapy of Faculty of Medicine, Public Health and Nursing, in collaboration with the Indonesian Society of Anesthesiology and Intensive Therapy , Yogyakarta Special Region Br, 2017)
Background : The effectiveness of tramadol and fentanyl as multimodal pain theraphy after surgery. Objective : The aim of this study is to compare the effectiveness of the addition of a continuous drip of tramadol is 0,125mg/kgbw /hour on a continuous fentanyl 1 ug/kg/h after the addition of bolus tramadol 50mg given every 6 hours in patients with fentanyl 1 ug/kgbw/hour as analgesia post operation. Methods : Thirty two patients who underwent surgery (oncology, gynecology and laminectomy) under general anesthesia were enrolled.. Samples were randomly divided into 2 groups TB and TK, each group contained 16 patients. In TK group got tramadol 0,125mg/kgbw/hour on a continuous fentanyl 1μg/kgbw/hour. TB group got Bolus tramadol 50 mg per 6 hours on a continuous fentanyl 1μg/kgbw/hour. Results : No significant clinical difference between VAS score TK Group and TB Group on minute 0, hour 6th and hour 12th (p > 0.05, p<0.05). Frequencies of additional fentanyl rescue at first 6 hour in TB group was 6 patients (37.5%), (VAS 4, 3 patients),(VAS 5, 2 patients), in TK group was 3 patients (18.8%), (VAS 4, 1 Patient), (VAS 5, 1 patient), (VAS 6, 1 patient). Additional of fentanyl rescue at second 6 hours in TB Group were 2 patients (12.5%), (VAS 4, 2 patients), in TK Group was 3 patients (18,8%), (VAS 4 , 2 patients) , (VAS 5, 1 patient). Conclusion : The addition of tramadol 0.125 mg/kgbw/h give the same effectiveness in clinical analgesia than tramadol intermittent bolus of 50 mg/6 hours in patients who received fentanyl 1 ug/kgbw/h for the treatment of postoperative pain